Risk of Zoonotic Transmission of COVID-19 during Eid-Ul-Fitr in Pakistan - Abdul Qader; Hamza Tariq; Muhammad Khawar Hayat (Health Dynamics, 2024)
Eid-ul-Fitr is an auspicious festival that is expected to celebrate by millions of Muslims across the world including Pakistan by the end of April. The Delta variant of COVID-19 is way more harmful than any other variants. The spread of virus still remains very high in large festival gatherings like Eid ul Fitr instead of strictly following SOPs. The mass migration of people across the country during festival is of main concern that leads to increase spread of virus. It is imperative that government officials along with community leaders, religious scholars and health authorities should take part in mitigating risks of virus transmission with serious measures. As general public is not much aware of the COVID-19 complications, it becomes significant to educate illiterate people through various approaches like to give them awareness about virus, its symptoms, preventive measures and significance of vaccination. Communication in their local language that is easily comprehendible and in persuasive way greatly impacts the public and empowers them to adapt healthy behavior that helps to mitigate the risk of virus transmission.